Just-in-Time Scheduling Models and Algorithms for Computer and Manufacturing Systems - Jozefowska, Joanna. (International Series in Operations Research & Management Science,, 2007)
As the field of Supply Chain Management has matured, maintaining the precise flow of goods to maintain schedules (hence, minimizing inventories) on a just-in-time basis still remains as a major challenge. This problem or challenge has resulted in a fair amount of quantitative research in the area, producing an array of models and algorithms to help ensure the precise flow of components and final products into inventories to meet just-in-time requirements. Just-in-Time Scheduling: Models and Algorithms for Computer and Manufacturing Systems is the first expository treatment surveying the theoretical work on computer systems models and algorithms utilized in just-in-time scheduling. With the impact of globalization and supply chains on manufacturing, there are immense amounts of material flowing through supply chains at any given time worldwide. Therefore the scheduling of all the stages of material arriving at different geographical points at precise times is a highly significant problem. Moreover, the theoretical work in this area has larger ramifications for operational scheduling in many application areas. The scheduling models and algorithms presented and illustrated in the book will be done so in the context of extensive use of computer systems in a "real time context." The "just-in-time" and "real-time" theoretical work in the book will be of value and interest to many Engineers, Computer Scientists and Operations Research/Management Science researchers, students and practitioners. The book will survey and synthesize all the research in this topical area.